Language in Humans and in Other Animals. Fabrici d’Acquapendente at the Crossroads between Medicine and Philosophy - Gensini, Stefano; Tardella, Michela (Theoria et Historia Scientiarum, 2016)
In this paper we give a comprehensive account of the three treatises that Girolamo Fabrici d’Acquapendente (1533–1619), an anatomist from that stronghold of naturalistic-experimental Aristotelianism known as the School of Padua, devoted to language topics. In De larynge (1600), the author described the structure and the functions of the breathing/phonatory apparatus from a comparative point of view, in order to identify both the analogies and the differences existing between humans and other animals. In De locutione (1601) Fabrici put forward a ‘philosophical’ analysis of speech, taking into account both its physical-articulatory features and its specific role in human life. In the third treatise, De brutorum loquela (1603), Fabrici, while re-discussing the Aristotelian distinction between phoné and diálektos, ascribed non human animals a peculiar kind of articulation going hand-in-hand with their states of mind. In so doing, Fabrici paved in advance the way for an alternative to Descartes’ distrust of the animal mind and its possibile linguistic counterparts.